Pelatihan Penelusuran E-Resources untuk Penyusunan Artikel Ilmiah bagi Guru-Guru di Kabupaten Tuban - Imas Cintamulya; Mu'jizatin Fadiana (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
Training in researching e-resources for the preparation of scientific articles for teachers in the Tuban district has been carried out. Teachers in the Tuban district have received training in researching e-resources for the preparation of scientific articles. This activity is carried out as an effort to improve teacher professionalism in writing scientific articles. This training aims to provide understanding and skills in researching e-resources for the preparation of scientific articles for teachers in Tuban Regency. This training participant is limited to 15 people, considering that they are still in a COVID-19 condition. The method used is a lecture combined with a discussion during the socialization. The demonstration method is carried out during the e-resources research activities. Meanwhile, to record the activities of training participants through documentation. Based on the assignment to search for articles from Science Direct, Google Advance, Garuda, Library Genesis, Sinta, DOAJ, and Scopus, the results showed that all participants scored above 90 on average. Resources for finding scientific articles of research results are very good.